Effect of Vaccination Outer Membrane Protein 52 kDa on Changes in Erythrocyte Index of Tilapia (Oreochromis niloticus) Infected by Aeromonas hydrophila - Nurrahmad, Nanda Rino; Yuliani, M. Gandul Atik; Ernawati, Rahaju; Chusniati, Sri; Herupradoto, Eduardus Bimo Aksono; Wahyuni, Retno Sri (Universitas Airlangga, 2021)
The purpose of this study was to determine the effect after being vaccinated by OMP 52 kDa Aeromonas hydrophila for 1 week and then infected with Aeromonas hydrophila 10 CFU/mL for 4 days on changes in erythrocyte index. Tilapia (Oreochromis niloticus) used in this study was 10-12 cm long. There were 20 tilapia (Oreochromis niloticus) which were divided into 4 groups, consisting of 2 control groups and 2 treatment groups which were given various types of vaccine formulations. Group P0 (-) (unvaccinated and infected), Group P0 (+) (unvaccinated and infected), group P1 (vaccinated with the whole cell protein